Case Report: Delayed Ventricular Pseudoaneurysm After Radiofrequency Ablation of Left Posteromedial Papillary Muscle Ventricular Tachycardia - Kim, Min; Park, Yoon Jung; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Pak, Hui-Nam; Lee, Moon-Hyoung (Frontiers in Cardiovascular Medicine, 2022)
A 74-year-old woman presented with incessant wide complex tachycardia that was refractory to cardioversions. Successful radiofrequency catheter ablation was performed on the left ventricular posteromedial papillary muscle. An inaudible steam pop has occurred during the procedure, but we confirmed that there were no complications during the procedure and short-term follow-up of echocardiography. Two months after the procedure, an asymptomatic pseudoaneurysm was identified at the ablation site that had not been observed in the short-term follow-up.